Effect of Solution Conditions on the Properties of Sol–Gel Derived Potassium Sodium Niobate Thin Films on Platinized Sapphire Substrates - Alexander Tkach; André Santos; Sebastian Zlotnik; Ricardo Serrazina; Olena Okhay; Igor Bdikin; Maria Elisabete Costa; Paula M. Vilarinho (Nanomaterials, 2019)
If piezoelectric micro-devices based on K0.5Na0.5NbO3 (KNN) thin films are to achieve commercialization, it is critical to optimize the films’ performance using low-cost scalable processing conditions. Here, sol−gel derived KNN thin films are deposited using 0.2 and 0.4 M precursor solutions with 5% solely potassium excess and 20% alkali (both potassium and sodium) excess on platinized sapphire substrates with reduced thermal expansion mismatch in relation to KNN. Being then rapid thermal annealed at 750 °C for 5 min, the films revealed an identical thickness of ~340 nm but different properties. An average grain size of ~100 nm and nearly stoichiometric KNN films are obtained when using 5% potassium excess solution, while 20% alkali excess solutions give the grain size of 500−600 nm and (Na + K)/Nb ratio of 1.07−1.08 in the prepared films. Moreover, the 5% potassium excess solution films have a perovskite structure without clear preferential orientation, whereas a (100) texture appears for 20% alkali excess solutions, being particularly strong for the 0.4 M solution concentration. As a result of the grain size and (100) texturing competition, the highest room-temperature dielectric permittivity and lowest dissipation factor measured in the parallel-plate-capacitor geometry were obtained for KNN films using 0.2 M precursor solutions with 20% alkali excess. These films were also shown to possess more quadratic-like and less coercive local piezoelectric loops, compared to those from 5% potassium excess solution. Furthermore, KNN films with large (100)-textured grains prepared from 0.4 M precursor solution with 20% alkali excess were found to possess superior local piezoresponse attributed to multiscale domain microstructures.